Pengaruh Penyajian Laporan Keuangan dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Keuangan Daerah (Studi pada SKPD Kota Tasikmalaya Tahun 2019) - Sabriani, Ajeng Ayu; Rahayu, Sri (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
This study was conducted to analyze the effect of presenting financial statements and internal control systems simultaneously and partially on the accountability of regional financial management in the Tasikmalaya City SKPD in 2019. This study uses the presentation of financial statements and internal control system as independent variables, and the accountability of regional financial management as dependent variable. Data analysis method used is multiple regression analysis. This study shows that the presentation of financial statements and internal control systems has a significant positive effect simultaneously on the accountability of regional financial management. The financial statement presentation partially has a significant positive effect, and the internal control system partially has a significant positive effect on the accountability of regional financial management. Keywords: Presentation of Financial Statements, Internal Control Systems, Accountability of Regional Financial Management.